Evaluasi Radiografi Hubungan Kelainan Sendi Temporomandibular dengan Maloklusi pada Penderita Nyeri Kepala - Evy Savitri Baskara; Heru Suryonegoro (Faculty of Dentistry, Universitas Indonesia, 2015)
Headache could be a symptom of many disturbances or alterations influencing mastication system. It had been reported that one out of three persons had experienced severe headache in his or her lige. According to many research, 70% patients with temporomandibular disorder has a recurrent headache symptom. Furthermore, a temporomandibular disorder with headache could be resulted from alteration in occlusion. Unfortunately, examination for occlusal disturbances that cause temporomandibular disorder is often neglected. Many dentists assume that patient with such a symprom should consult a physician since it is beyond his area of treatment. This present study is aimed to look for any relationship between alteration in radiographic imaging of temporomandibular joint, and occlusal disturbance in individuals with headacehe symptom, using questioners and study models. The study also includes clinical examination to see any alteration in occlusal function, and radiograph of temporomandibular joint to see any differences from normal. Data that had been collected is analyzed by statistical analysis to find relationship between the two variables.